Salvando e aprendendo com megalobulimus: uma análise da evolução do projeto e das pesquisas envolvidas - Pecora, Iracy Lea [UNESP]; Correia, Lucas Vilas Bôas [UNESP]; Miranda, Marcel Sabino (Universidade Estadual Paulista (Unesp), 2015)
Megalobulimus is one of most diverse genus of Brazilian land snail fauna. It has as threats to their conservation degradation of the natural environment and the introduction of invasive species such as the giant African snail, Achatina fulica. So, given the discovery of two species living in the same anthropic environment, M. paranaguensis and A. fulica, arose the idea of studying the relationships between them. These observations included the verification of the elimination of both species control campaigns African snail. Thus it was started an environmental education project involving the two species, the creation of a moluscário and a research laboratory in molluscs, which will be analyzed in this work. The project has proved to be an important tool for discussion, production and dissemination of knowledge on this issue, serving 3,578 students from 64 primary schools of São Vicente and Praia Grande, as well as about 2,500 participants from 24 professions fair (high school students). Up to now, 5 scholarship students PROEX / UNESP and 5 volunteers participated in the project; 3 students performed scientific projects, with 2 FAPESP grants. The moluscário currently has 59 individuals of M. paranaguensis adding the initial individuals and those born in the CLP; in all, there were 46 births. These results reinforce that teaching, research and extension are inseparable, and that together help in the full development of good students and professionals.

Megalobulimus é um dos gêneros mais diversos da fauna brasileira de moluscos terrestres. Possui como ameaças à sua conservação, a degradação do ambiente natural e a introdução de espécies invasoras, como o caracol gigante africano, Achatina fulica. Por isso, tendo em vista a descoberta de duas espécies convivendo no mesmo ambiente antropizado, M. paranaguensis e A. fulica, surgiu a ideia de se estudar as relações entre eles. Essas observações incluíram a constatação da eliminação de ambas espécies em campanhas de controle do caracol africano. Assim, foi iniciado um projeto de Educação Ambiental envolvendo as duas espécies, a criação de um moluscário e um laboratório de pesquisa em moluscos, que será analisado neste trabalho. O projeto revelou-se como uma importante ferramenta para discussão, produção e disseminação de conhecimento acerca desta problemática, atendendo até o momento 3.578 alunos de 64 escolas de Ensino Fundamental de São Vicente e Praia Grande, além de aproximadamente 2.500 participantes de 24 Feiras de Profissões (alunos do Ensino Médio). Até o momento, 5 alunos bolsistas PROEX/UNESP e 5 voluntários participaram do projeto; 3 alunos realizaram projetos de iniciação científica, com 2 bolsas FAPESP. O moluscário possui atualmente 59 indivíduos de M. paranaguensis somando-se as matrizes e os nascidos no CLP; ao todo, foram registrados 46 nascimentos. Esses resultados reforçam que ensino, pesquisa e extensão são indissociáveis, e que em conjunto auxiliam na formação plena de bons alunos e profissionais.
Keywords: Environmental education; Arua; Conservation; Educação ambiental; Aruá; Conservação